IMPROVEMENT OF TECHNOLOGY FOR OBTAINING BONDING WATER-SOLUBLE POLYMERS FOR COLORING OF MIXED FABRICS (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Changes in the color intensity index (K/S) from the concentration of components in the composition have been studied. It was found that the intensity of coloring of silk-acetate fabric with dyed dispersed ruby C mainly depends on the concentration of binders in the compositions. The dependence of the intensity of coloring on the temperature during dyeing is determined by the example of various dispersed dyes.